The Road to International Protection: An Overview on International, European, and Icelandic Refugee and Asylum Legislation and Pressing Human Rights Challenges - Ingunn Sigríður Árnadóttir 1990- (2016)
The global issue of international protection for refugees and asylum seekers has become one of the great challenges of the international community. The aim of this thesis is to research the sources of refugee and asylum law as well as contentious issues in the application of those laws from a human rights perspective. The thesis is divided into three principal parts: Firstly, the international context of refugee and asylum law is examined by studying the relevant international instruments, centering around the core legal instrument that is the Convention relating to the Status of Refugees from 1951 and its 1967 Protocol (Refugee Convention). Secondly, focus is laid on regional instruments of refugee and asylum law in Europe, most prominently the Common European Asylum System (CEAS). The importance of Article 3 of the European Convention on Human Rights (ECHR), which has been considered to entail the principle of non-refoulement, is also especially emphasized. Even though the Refugee Convention and international human rights law remain the core foundation, the asylum legislation of the EU offers a considerable addition to the asylum system in that region in terms of more precise definitions of concepts and more detailed procedures. Thirdly and finally, the research is narrowed down to the national instruments of refugee and asylum law in Iceland. This is done in order to present how national asylum legislation functions in practice and in context with both international and regional asylum and human rights law. Iceland is not an EU Member State but still participates in European cooperation through the Schengen scheme and Dublin cooperation, as well as it has incorporated the ECHR into its legislation. Furthermore, Icelandic asylum legislation is under considerable influence of the CEAS. The main conclusion from examining these different instruments of international protection is that asylum legislation seems to be less a protection scheme for the human rights of those forced to flee their home countries in ...